Simulation test of automotive intake valve using computer aided engineering software - Hafierul Hafiz, Md Razi (2008)
Analysis of stress with different material in intake valve is the main purpose of this project. This research was carried about the stress impact in intake valve head where the most wear would occur at particular different RPM. The study of this thesis is based on previous research in intake valve stress and fatigue by experiment. Without actual experiment, intake valve stress can be analyzing by simulation using ALGOR software and specific RPM with specific maximum cylinder pressure can be calculated via GT-POWER software. Three most common intake valve materials was tested to be compared between stress which are common steel intake valve material, ceramic intake valve material and titanium alloy intake valve material. The best material for intake valve within the three material tested would be titanium alloy intake valve. Titanium alloy material properties shown a very low impact of Von Mises Stress 173.6537 Mpa compared to ceramic intake valve 184.1683 Mpa and steel intake valve 179.0992 Mpa at the constant given load 16614.9411 N in 2000 RPM and temperature 300o C. The stress effect at intake valve seat showed the highest stress impact of Von Mises Stress at all intake valve material. It also shown a possible of wear happened in a form of ring around intake valve seat.